Music in English language teaching - Kotvanová, Andrea (Univerzita Pardubice, 2024)
This thesis focuses on teaching vocabulary at primary school with the use of songs. The theoretical part will define the basic aim of teaching English in relation to linguistic competences. Then, the principles of teaching vocabulary will be covered. In the theoretical part, a set of criteria will be laid out. Based on the presented criteria, the author will create sets of activities with the implementation of songs to test whether songs are sufficient material to be implemented into teaching vocabulary followed by a commentary.
Hudba ve výuce anglického jazyka
Keywords: populární písně; výuka slovní zásoby; lingvistická kompetence; obecný cíl výuky anglického jazyka; vývojová psychologie; principy výuky slovní zásoby; popular songs; teaching vocabulary; elementary school; linguistic competences; aim of English language teaching; developmental psychology; principles of teaching vocabulary